Increasing vertical jump - Hutchinson, M.
M. Hutchinson, M.D., chief of sports medicine for the UIC teams discusses the use of water-resistance training and spring-controlled body conditioning to improve the leaping ability of athletes. "We did a study to try to improve the leaping ability in the elite rhythmic gymnasts of the United States team, the US National Team. If they have a better leaping ability they will score higher and look better. So our goal was to improve their leaping ability through a course of jump training. In addition what we wanted to guarantee we were not going to cause any new injuries so we wanted to avoid any possibility of overuse injuries just because of our training. We designed a training program for the US national team. We tested them prior to beginning the training, one month into the training, four months into the training to see how they progressed and see if we were making any significant inroads with the jump training. We tested them on a force plate that was produced by Probotics Incorporated. It's called an electronic vertical jump measuring system. The system has a little computer attached to it that will allow us to measure floor reaction time, a verage jump height, and explosive leg power. "